KEPASTIAN HUKUM HAK ATAS TANAH MASYARAKAT ADAT SUKU ANAK DALAM DI KAWASAN HUTAN - Reni Fatmala Sari; Sapto Hermawan; Andina Elok Puri Maharani (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
Forests are a mandate and gift from God Almighty bestowed on the Indonesian people. SAD live in groups in a community, and their lives cannot be separated from the forest and its natural surroundings. The root of conflict and neglect of MHA rights in forest areas is the lack of legal certainty regarding acknowledging the existence of MHA, customary areas, and traditional rights. The state also does not recognize the boundaries of customary territories, which results in the seizure of indigenous peoples' territories. This study aims to examine and analyze the certainty of land rights of indigenous tribal communities in forest areas. This research is normative legal research, using a statutory approach and sources of primary and secondary legal materials with data collection techniques, namely literature study, and analyzed qualitatively. The results obtained are that for the sake of realizing legal certainty, the rights of the SAD community must first be determined that SAD is included as one of the MHA and these elements meet the SAD to be recognized as MHA. However, in reality, SAD is not recognized as MHA; the rights to justice, protection, and legal clarity have been hampered by efforts to defend and defend their ulayat rights. The fundamental problem of MHA's territorial claims in forest areas stems from the absence of legal recognition as legal subjects